Pemanfaatan Smartphone Iphone dan Android untuk Akses Informasi Dakwah - Amala Ramadhan, Ahsanu (Journal of Islamic Communication Studies, 2025)
The use of smartphones among university students has significantly increased, particularly as a primary medium for accessing da’wa information and supporting digital learning. Students of the Communication Science Department at UIN Sunan Ampel Surabaya also rely on smartphones as a tool for digital literacy, through learning applications, educational social media content, and various information platforms. This study aims to compare the utilization of Android- and iPhone-based smartphones in accessing da’wa information. This research employs a qualitative method with a comparative study approach, supported by the Uses and Gratifications theory to explain users’ motives and satisfaction in media use. Data were collected through in-depth interviews with students who use Android and iPhone devices, and were analyzed using a descriptive-comparative technique. The findings indicate that both smartphones serve similar educational purposes, yet differ in user orientation and experience. Android users show advantages in terms of flexibility, affordability, and efficiency, while iPhone users benefit from faster access to references, system stability, and integrated features. Challenges identified include lagging and performance decline on Android, as well as overheating and limited storage capacity on iPhone. Overall, smartphone utilization plays a significant role in enhancing independent learning, widening access to da’wa information, and shaping adaptive digital learning practices among university students.